2015
DOI: 10.1007/s00425-015-2309-1
|View full text |Cite
|
Sign up to set email alerts
|

A deletion mutant ndv200 of the Bacillus thuringiensis vip3BR insecticidal toxin gene is a prospective candidate for the next generation of genetically modified crop plants resistant to lepidopteran insect damage

Abstract: Ectopic expression of a deletion mutant ( ndv200 ) of Bacillus thuringiensis vip3BR gene in tobacco plant provided almost complete protection against major crop pests cotton boll worm ( Helicoverpa armigera ), black cut worm ( Agrotis ipsilon ) and cotton leaf worm ( Spodoptera littoralis ). Whereas vip3BR transgenic tobacco plant failed to protect themselves from these insects and showed resistance towards cotton leaf worm only. An analogous form of the Bacillus thuringiensis vip3Aa insecticidal toxin gene, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
(30 reference statements)
2
9
1
Order By: Relevance
“… 50 suggested a putative cleavage site between residue Thr 10 and Arg 11 in Vip3Aa based on the S score prediction. Removal of N-terminal 12 amino acids (in Arg 12 ) was shown in Vip3Ab1 28 and we have here shown that the 20 kDa N-terminal fragment of Vip3Af1 is also cleaved after Arg 11 .…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“… 50 suggested a putative cleavage site between residue Thr 10 and Arg 11 in Vip3Aa based on the S score prediction. Removal of N-terminal 12 amino acids (in Arg 12 ) was shown in Vip3Ab1 28 and we have here shown that the 20 kDa N-terminal fragment of Vip3Af1 is also cleaved after Arg 11 .…”
Section: Discussionsupporting
confidence: 64%
“…4 ). The 20 kDa fragment, obtained after trypsin treatment of the Vip3Af1(WT) (and present in patterns “a”, “d”, and “e”), yielded the sequence ALPSF, the first amino acid corresponding to Ala 12 . The N-terminal sequence of the 62 kDa was DXXPA, which only matched with the query sequence on DSSPA (D = Asp 199 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 3-year study on the field performance of VipCot expressing just the Vip3Aa protein indicated that the plants were highly efficacious against H. armigera early in the season but that efficacy declined as the season progressed although not so drastically as Cry1Ac in Bollgard or Ingard cotton (117). In 2015, the first modified Vip3A protein, with improved toxicity, was introduced into tobacco, conferring almost total protection against H. armigera, A. ipsilon, and S. littoralis (118).…”
Section: Expression In Plantsmentioning
confidence: 99%
“…While Li et al [28] found that deletion of the N-terminal first 189 amino acids abolished the insecticidal activity of a chimeric Vip3AcAa protein, Gayen et al [35] found that a Vip3Aa deletion mutant lacking the first 200 amino acids of the protein not only did not abolish the activity, but it slightly enhanced it against the three insect species tested, and that the expression of this deleted protein in tobacco plants provided even higher plant protection against several feeding insects than the expression of the wild type protein [36]. It is possible that the discrepancy between these two studies is due to the method used for the expression and purification of the deletion mutants, if not to the different Vip3A proteins used.…”
Section: Discussionmentioning
confidence: 99%